Coexpression network and trans‐activation analyses of maize reproductive phasiRNA loci. (10th December 2022) - Zhan, Junpeng; O'Connor, Lily; Marchant, D. Blaine; Teng, Chong; Walbot, Virginia; Meyers, Blake C.
SUMMARY: The anther‐enriched phased, small interfering RNAs (phasiRNAs) play vital roles in sustaining male fertility in grass species. Their long non‐coding precursors are synthesized by RNA polymerase II and are likely regulated by transcription factors (TFs). A few putative transcriptional regulators of the 21‐ or 24‐nucleotide phasiRNA loci (referred to as 21‐ or 24‐PHAS loci) have been identified in maize ( Zea mays ), but whether any of the individual TFs or TF combinations suffice to activate any PHAS locus is unclear. Here, we identified the temporal gene coexpression networks (modules) associated with maize anther development, including two modules highly enriched for the 21‐ or 24‐PHAS loci. Comparisons of these coexpression modules and gene sets dysregulated in several reported male sterile TF mutants provided insights into TF timing with regard to phasiRNA biogenesis, including antagonistic roles for OUTER CELL LAYER4 and MALE STERILE23. Trans ‐activation assays in maize protoplasts of individual TFs using bulk‐protoplast RNA‐sequencing showed that two of the TFs coexpressed with 21‐PHAS loci could activate several 21‐nucleotide phasiRNA pathway genes but not transcription of 21‐PHAS loci. Screens for combinatorial activities of these TFs and, separately, the recently reported putative transcriptional regulators of 24‐PHAS loci using single‐cell (protoplast) RNA‐sequencing, did not detect reproducible activation of either 21‐PHAS or 24‐PHAS loci. Collectively, our results suggest that the endogenous transcriptional machineries and/or chromatin states in the anthers are necessary to activate reproductive PHAS loci. Significance Statement: This work identifies the temporal gene coexpression networks associated with maize anther development, including two modules highly enriched for the 21‐ or 24‐nucleotide reproductive phased, small interfering RNA (phasiRNA) loci. Trans ‐activation assays of putative transcriptional regulators of the phasiRNA loci using bulk and single‐cell RNA‐sequencing suggest that endogenous transcriptional machineries and/or chromatin states in the anthers are necessary to activate reproductive phasiRNA loci.